Psychological Abuse and Its Correlates among Elderly Peoples of Saudhiyar Village Dang Nepal - Bijay Aryal, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Psychological Abuse and Its Correlates among Elderly Peoples of Saudhiyar Village Dang Nepal